E-035 Endovascular treatment of wide-necked intracranial aneurysms with the scepter XC balloon and low-profile visualized intraluminal support (LVIS) JR. device. (22nd July 2018) - Wallace, A; Kayan, Y; Almandoz, J Delgado; Fease, J; Milner, A; Scholz, J; Thomas, M
Abstract : Background: The Scepter XC balloon catheter can be used for balloon-assisted coiling (BAC) of cerebral aneurysms, but also accommodates delivery of a low profile visible intraluminal stent (LVIS Jr.). We assessed the safety and effectiveness of BAC using the Scepter XC, with LVIS Jr. stent-assisted coiling (SAC) as a bailout option. Methods: A single-institution prospectively-maintained neurointerventional database was retrospectively reviewed for wide-necked (neck width ≥4 mm or dome-to-neck ratio <2) saccular aneurysms treated using the Scepter XC. Complication and angiographic occlusion rates of BAC and SAC procedures were compared. Multivariate logistic regression was used to identify variables predictive of complete aneurysm occlusion at last angiographic follow up. Results: The cohort included 169 wide-necked saccular intracranial aneurysms treated in 157 procedures. SAC was used to treat 25% of aneurysms by deploying the LVIS Jr through the Scepter XC. The overall procedural complication rate was 11%, including 3.2% rates of symptomatic thromboembolic and hemorrhagic complications, with no significant differences in complications between BAC and SAC procedures (p=0.26). The overall complete aneurysm occlusion rate was 59%, with trends toward higher complete aneurysm occlusion and lower retreatment rates with SAC (78 vs 54%, p=0.07; 0 vs 9.3%, p=0.10). Multivariate logistic regression identified aneurysm size, procedure technique (BAC or SAC), and duration of follow up as independent predictors of complete aneurysm occlusion. Conclusions: Initial experience using the Scepter XC for BAC, with LVIS Jr. SAC as a bailout option, demonstrates acceptable angiographic and clinical results. Disclosures: A. Wallace: None. Y. Kayan: 2; C; Medtronic, Penumbra, Microvention. J. Delgado Almandoz: 2; C; Medtronic, Penumbra, Microvention, Accriva. J. Fease: None. A. Milner: None. J. Scholz: None. M. Thomas: None.